2007
DOI: 10.1128/aac.00524-07
|View full text |Cite
|
Sign up to set email alerts
|

Antiprion Activity of Cholesterol Esterification Modulators: a Comparative Study Using Ex Vivo Sheep Fibroblasts and Lymphocytes and Mouse Neuroblastoma Cell Lines

Abstract: Our studies on the role of cholesterol homeostasis in the pathogenesis of scrapie revealed abnormal accumulation of cholesterol esters in ex vivo peripheral blood mononuclear cells (PBMCs) and skin fibroblasts from healthy and scrapie-affected sheep carrying a scrapie-susceptible genotype compared to sheep with a resistant genotype. Similar alterations were observed in mouse neuroblastoma N2a cell lines persistently infected with mouse-adapted 22L and RML strains of scrapie that showed up to threefoldhigher ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 38 publications
5
31
0
Order By: Relevance
“…These results confirm and extend our previous findings in the same cell model [14] and in the ovine scrapie [11][12][13], and further support the presence of a tight association between prion infection/susceptibility and altered cholesterol homeostasis. In agreement with our results, altered cholesterol metabolism/esterification with over-expression of ACAT-1 (soat1) was reported in mice brains during the course of experimental scrapie [34, refs therein], and up-regulation of cholesterol biosynthesis was recently described following prion A total of 30x10 6 of each cell culture was collected from sub-confluent flasks.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…These results confirm and extend our previous findings in the same cell model [14] and in the ovine scrapie [11][12][13], and further support the presence of a tight association between prion infection/susceptibility and altered cholesterol homeostasis. In agreement with our results, altered cholesterol metabolism/esterification with over-expression of ACAT-1 (soat1) was reported in mice brains during the course of experimental scrapie [34, refs therein], and up-regulation of cholesterol biosynthesis was recently described following prion A total of 30x10 6 of each cell culture was collected from sub-confluent flasks.…”
Section: Discussionsupporting
confidence: 82%
“…The effect on intracellular lipids of a drug combination with marked anti-PrP res synergism, such as everolimus (EVE, 0.02 µM) and chlorpromazine (CP, 2 µM), was evaluated by staining the cells with dyes with affinity for different lipids (Oil Red O for neutral lipids; Nile red for neutral lipids and phospholipids; Filipin for free cholesterol). As expected [14], Oil Red O (ORO) staining revealed significantly higher neutral lipids (NL) in the 22L-infected than in the uninfected N2a cells ( Figure 4A and B). However, both single and combined drug treatments markedly reduced red ORO intensity in the 22L-infected cell line.…”
Section: Effect Of Single Vs Dual-drug Combinations On Intracellularmentioning
confidence: 49%
See 2 more Smart Citations
“…In more recent reports, we have shown that prion infection significantly increases levels of free cholesterol and of cPLA 2 in neuroblastoma cell lines (Bate et al, 2008c). Moreover, abnormal accumulation of cholesterol esters in peripheral cells has been observed in scrapie-infected sheep and treatment with compounds known to interfere with cholesterol homeostasis lead to significant reduction of cholesterol esters in these cells (Pani et al, 2007), indicating that cholesterol esterification is an important component in the protection against prion-mediated cell death (Bate et al, 2008a). In this present study, epitope-specific anti-prion antibodies (Beringue et al, 2003) have been utilized on cell culture models (Pleasure et al, 1992) on rat dorsal root ganglia neurons (DRG) and mouse primary cortical neurons (MPCN) in order to assess antibody-mediated effects on cholesterol homeostasis.…”
Section: Introductionmentioning
confidence: 99%